The report card - Clements, Andrew, 1949-2019- (Simon & Schuster Books for Young Readers, 2004)
Fifth-grader Nora Rowley has always hidden the fact that she is a genius from everyone because all she wants is to be normal, but when she comes up with a plan to prove that grades are not important, things begin to get out of control.